Tetraspanins as therapeutic targets in hematological malignancy: a concise review - Beckwith, Kyle A.; Byrd, John C.; Muthusamy, Natarajan (Frontiers in Physiology, 2015)
Tetraspanins belong to a family of transmembrane proteins which play a major role in the organization of the plasma membrane. While all immune cells express tetraspanins, most of these are present in a variety of other cell types. There are a select few, such as CD37 and CD53, which are restricted to hematopoietic lineages. Tetraspanins associate with numerous partners involved in a diverse set of biological processes, including cell activation, survival, proliferation, adhesion, and migration. The historical view has assigned them a scaffolding role, but recent discoveries suggest some tetraspanins can directly participate in signaling through interactions with cytoplasmic proteins. Given their potential roles in supporting tumor survival and immune evasion, an improved understanding of tetraspanin activity could prove clinically valuable. This review will focus on emerging data in the study of tetraspanins, advances in the clinical development of anti-CD37 therapeutics, and the future prospects of targeting tetraspanins in hematological malignancy.